Challenging the Objectivist Paradigm: Teaching Biblical Theology with J.R.R. Tolkien, C.S. Lewis, and Guillermo del Toro - Lief, Jason (Teaching theology and religion, 2009)
The dissimilarity that exists between the historical and cultural situation of North American college students and the world described by the biblical authors poses a problem for theological and religious education. While the biblical authors tell fantastic stories of miracle and magic, the scientific and technological paradigm prevalent in western culture emphasizes the gathering of objective facts in the name of efficiency and pragmatism. Theological education tends to respond to this situation by embracing either a program of historical criticism or a form of Biblicism, both of which reinforce an objectivist approach to education. What is needed in theological education is an approach that “re-mythologizes” the Bible, enabling students to hear the theological message of the text addressed to their cultural and historical situation. One way this approach can be encouraged is through the teaching of the biblical text in conversation with the contemporary stories found in popular culture.